MindRegulation SEL: effects of relaxation and guided imagery interventions with socioemotional learning content in the physiologic well-being (heart rate variability) of children - Galinha, I. C.; Lima, Catarina; Hugo Plácido da Silva; Pinal, D.; Arriaga, P. (XIV Congreso de la Sociedad Española de Psicofisiología y Neurociencia Cognitiva y Afectiva (SEPNECA), 2025)
Background: Relaxation and guided imagery interventions are inexpensive and research supports their effectiveness on health outcomes, impacting physiologic wellbeing indicators, such as heart rate variability. This RCT aims to test the benefits of an intervention comprising breathing, progressive muscle relaxation, and guided imagery with socioemotional learning content (MR-SEL). Method: The MR-SEL intervention was implemented for 15 minutes at the beginning of classes, for five months (30-39 sessions). Its effects were measured on a range of psychosocial, physiological, and cognitive outcomes. Seventeen classes (259 students, 3rd and 4th graders) were randomly assigned to three conditions: (a) MR-SEL; (b) relaxation; and (c) waitlist control. Data was collected four times: pretest, intermediate, post-test, and a six-month follow-up. Physiological indicators were collected in class, derived from Electrocardiogram (ECG) recordings of Heart Rate (HR) and Heart Rate Variability (HRV), monitored using portable Bitalino sensors. The validity of the measures was tested by comparing average levels of HR and HRV against reference values for that age range. Results: General linear model analysis showed a significant HR decrease and HRV increase, from the pre-test to the intermediate time in the MR-SL group, compared with the relaxation and control groups, which remained stable through the four data collection times. From the intermediate to the post-test times, the positive effects in HR and HRV slightly decreased, but were not statistically significant. Discussion: Results corroborate the hypothesis that the MR-SL affect the physiologic well-being of children, although they are small and transient.